Intercropping with Switchgrass Improves Net Greenhouse Gas Balance in Hybrid Poplar Plantations on a Sand Soil. Issue 4 (31st August 2017) - Collins, H.P.; Fay, P.A.; Kimura, E.; Fransen, S.; Himes, A.
Abstract : Core Ideas: A critical issue in the production of biofuels has been the competition with food crops Intercropping switchgrass and hybrid poplar was found to be a viable bioenergy production strategy Intercropped biomass production offset increases in GHGs and GWP N2O emissions factors averaged 1% of the applied N over the study In the Pacific Northwest, commercial hybrid poplar ( Populus generosa Henry × Populus canadensis Moench.) is managed at low stocking densities under irrigation for high‐value timber production. The objectives of this study were to measure greenhouse gas emissions (CH4, CO2, and N2 O) during intercropping of switchgrass ( Panicum virgatum L.) with hybrid poplar; estimate losses of fertilizer‐N as N2 O, and estimate global warming potentials (GWP) of the intercrop. Cumulative above‐ground biomass‐C of the poplar monoculture (PM) closely matched the four year growing season (GS) soil CO2 –C emissions, where aboveground biomass of the switchgrass monoculture (SM) and intercrop (IC) exceeded GS CO2 –C emissions by 14.1 Mg C ha ‐1 . Soil CH4 –C uptake was not significantly different between treatments, while GS N2 O‐N emissions for PM were ∼80% lower than both IC and SM. N2 O emissions factors averaged 0.7% of the applied N‐fertilizer. Cumulative contributions of CO2 emissions to GWP were offset by biomass‐C resulting in a near zero balance (−5.1 Mg CO2eq ha ‐1 ) for the PM, where, IC and SM sequestered significantly more CO2 resulting in a net GWP of −42.5 and –32.2 Mg CO2eq ha ‐1, respectively. Intercropping with switchgrass can improve the net greenhouse gas balance of hybrid poplar. Continued research is needed on the effects of irrigated bioenergy production on GHG emissions in intercropped systems as they will become increasingly important as agricultural water use, water availability and quality are challenged by climate change.